Nonlinear oscillations of fourth order quasilinear ordinary differential equations - Kamo, Ken-ichi; Usami, Hiroyuki (Acta mathematica Hungarica, 2011)
We consider fourth order quasilinear ordinary differential equations. Firstly, we classify positive solutions into four types according to their asymptotic properties. Then we derive existence theorems of positive solutions belonging to each type. Using these results, we can obtain an oscillation criterion, which is our main objective. Moreover, applying such criteria for ordinary differential equations to binary elliptic systems, we establish nonexistence theorems for positive solutions.